Business positioning and re-engineering methodology - Chong, Kaspar Kwong Liong. (2009)
Organisations are evolving. Changes happen out of response to market requirements (customer specification) or internal desire to enhance an organizations competitiveness. In the process of change, organisations are faced with the issue of managing the change and, more importantly, ensuring that the changes deliver improvements.